2017
DOI: 10.1002/jcla.22221
|View full text |Cite
|
Sign up to set email alerts
|

RHD alleles among pregnant women with serologic discrepant weak D phenotypes from a multiethnic population and risk of alloimmunization

Abstract: Background A considerable number of RHD alleles responsible for weak and partial D phenotypes have been identified. Serologic determination of these phenotypes is often doubtful and makes genetic analysis of RHD gene highly desirable in transfusion recipients and pregnant women. We analyzed the RHD gene in a cohort of pregnant women with doubtful D phenotypes. Methods RHD genotyping was performed on 104 cases with D typing discrepancies or with history of serologic weak D phenotype. Laboratory‐developed DNA te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 24 publications
0
17
0
1
Order By: Relevance
“…*The reason for recommending the transfusion of D-positive units for individuals bearing these variants was based on the lack of alloimmunization reports rather than on definite evidences that they are not prone to anti-D development performing the molecular investigation. 11,25 All studies were concordant with respect to the high prevalence of RHD*DAR and to the relatively lower representability of RHD*weak D types 1, 2, and 3 among…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations
“…*The reason for recommending the transfusion of D-positive units for individuals bearing these variants was based on the lack of alloimmunization reports rather than on definite evidences that they are not prone to anti-D development performing the molecular investigation. 11,25 All studies were concordant with respect to the high prevalence of RHD*DAR and to the relatively lower representability of RHD*weak D types 1, 2, and 3 among…”
Section: Discussionmentioning
confidence: 56%
“…Previous studies have also evaluated the frequency of D variants among Brazilian donors and patients, but with different criteria for performing the molecular investigation . All studies were concordant with respect to the high prevalence of RHD*DAR and to the relatively lower representability of RHD*weak D types 1, 2, and 3 among Brazilian donors with weak‐D phenotype.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…This amino acid change was predicted within the eighth membrane passage. Review of previously reported RHD variants at p.241 showed two known D variants: RHD*weak D type 67 (c.722C>T, p.Thr241Ile) associated with a cDE haplotype 2 and RHD*DEL45(c. 721A>C,p.Thr241Pro, which resulted in extremely weakened D expression) 3 . These three amino acid replacements were predicted to have a “deleterious effect” on protein function by PROVEAN and being “probably damaging” by PolyPhen2.…”
Section: Resultsmentioning
confidence: 99%